2022
DOI: 10.3390/jof8101017
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Regulators Enhance the Yield and Stress Resistance of Chlamydospores of the Biocontrol Agent Trichoderma harzianum T4

Abstract: Trichoderma strains have been successfully used in plant disease control. However, the poor stress resistance of mycelia and conidia makes processing and storage difficult. Furthermore, they cannot produce chlamydospores in large quantities during fermentation, which limits the industrialization process of chlamydospore preparation. It is important to explore an efficient liquid fermentation strategy for ensuring chlamydospore production in Trichoderma harzianum. We found that the addition of mannitol, glycine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A proteomic analysis revealed that the volatile organic compounds produced by biocontrol Bacillus amyloliquefaciens SQR-9 reduced the carbohydrate and amino acid metabolism of the protein of the tomato wilt pathogen Ralstonia solanacearum [ 49 ]. Moreover, the exogenous addition of mannitol and trehalose increased the production of chlamydospores of biocontrol fungal strains of T. harzianum T4, and enhanced their stress resistance by regulating lipid metabolism, indicating that lipid metabolism is an essential component of chlamydospore production and affects the stress resistance of chlamydospores [ 50 ]. These changes observed in the amino acid and lipid metabolism pathways may be related to the resistance of bacterial communities in strawberry stems and leaves to Fusarium infection.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic analysis revealed that the volatile organic compounds produced by biocontrol Bacillus amyloliquefaciens SQR-9 reduced the carbohydrate and amino acid metabolism of the protein of the tomato wilt pathogen Ralstonia solanacearum [ 49 ]. Moreover, the exogenous addition of mannitol and trehalose increased the production of chlamydospores of biocontrol fungal strains of T. harzianum T4, and enhanced their stress resistance by regulating lipid metabolism, indicating that lipid metabolism is an essential component of chlamydospore production and affects the stress resistance of chlamydospores [ 50 ]. These changes observed in the amino acid and lipid metabolism pathways may be related to the resistance of bacterial communities in strawberry stems and leaves to Fusarium infection.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was composed of six treatments: control, the three biocontrol agents, and two treatments of conventional fungicides under R. solani-infected soils and nontreated soils, thus 12 groups were produced. Surface sterilized coriander seeds were soaked for 2 h before sowing in a suspension of each biocontrol agent separately: T. harzianum (5 × 10 6 CFU/mL) [92], B. subtilis (1 × 10 8 bacterial CFU/mL), and P. fluorescens suspension (9 × 10 8 CFU/mL) (v/w) [93,94]. For fungicide treatments, coriander seeds were soaked in the IC 90 of each fungicide (Rizolex-T 50% WP and Amistar 25% SC).…”
Section: Assay Of Proteasementioning
confidence: 99%
“…This strain can effectively control the plant disease caused by B. cinerea [ 12 ], promote plant growth and increase crop yield [ 13 , 14 ]. In our previous study, we optimized the culture conditions for T. harzianum T4 and improved the yield of the T. harzianum biocontrol agent [ 15 ]. However, the research on its biocontrol mechanism is not comprehensive, particularly the mechanism of mycoparasitism.…”
Section: Introductionmentioning
confidence: 99%